2020
DOI: 10.1007/978-3-030-60067-9_2
|View full text |Cite
|
Sign up to set email alerts
|

On the Complexity of Learning Description Logic Ontologies

Abstract: Ontologies are a popular way of representing domain knowledge, in particular, knowledge in domains related to life sciences. (Semi-) automating the process of building an ontology has attracted researchers from different communities into a field called "Ontology Learning". We provide a formal specification of the exact and the probably approximately correct learning models from computational learning theory. Then, we recall from the literature complexity results for learning lightweight description logic (DL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It has been shown that the EL fragments EL lhs and EL rhs -the EL fragments that allow only conjunctions of concept names on the right-side and on the left-side of CIs, respectively-are polynomial time exactly learnable from entailments [23,24,38,37] 4 , however, this is not the case for EL. The learning framework is the one in Example 1 and the problem statement is the same as in the original approach.…”
Section: Building DL Ontologiesmentioning
confidence: 99%
“…It has been shown that the EL fragments EL lhs and EL rhs -the EL fragments that allow only conjunctions of concept names on the right-side and on the left-side of CIs, respectively-are polynomial time exactly learnable from entailments [23,24,38,37] 4 , however, this is not the case for EL. The learning framework is the one in Example 1 and the problem statement is the same as in the original approach.…”
Section: Building DL Ontologiesmentioning
confidence: 99%